Conductometric determination of sibutramine HCl, sumatriptan succinate and lomefloxacine HCl and the solubility products of their ion associates with molybdophosphoric acid - Ayad, Magda Mohamed; Abdellatef, Hisham Ezzat; Hosny, Mervat Mohamed; Kabil, Nagla Abdel-Sattar (European Journal of Chemistry, 2013)
Conductometric determination of sibutramine HCl, sumatriptan succinate and lomefloxacine HCl with molybdophosphoric acid as a precipitating reagent was investigated. Various experimental conditions were evaluated and results obtained showed good recoveries, (mean recovery values of 100.51, 99.68, 99.41 and relative standard deviation of 0.332, 0.404, 0.509 for sibutramine HCl, sumatriptan succinate and lomefloxacine HCl, respectively). Numerical derivatization (first and second derivative) of the data was also applied, showing more accurate results compared to classical ones. The described procedures allowed the determination of equilibrium constants those indicated high degree of completeness of the precipitation reaction. Other parameters related to ion pair complex such as solubility and solubility product were also calculated. The described procedures allowed the determination of the studied drugs in the range of 5-15 mg. The precipitate obtained by ion pairing of lomefloxacine HCl with molybdophosphoric acid was spectroscopically characterized using IR. The method was further applied successively to pharmaceutical formulations, the proposed method offering a high degree of accuracy and precision when compared to reference methods.